Bridging abstract concepts and digital literacy: Empowering high school students through ChemDraw training - Retno Agnestisia; Rizki Rachmad Saputra; Marvin Horale Pasaribu; Yuliana Yuliana; Rini Sundari (Community Empowerment, 2026)
High school chemistry learning often struggles with abstract concepts such as molecular structures, chemical bonding, and reaction mechanisms. Utilizing chemical software like ChemDraw offers a viable solution; however, preliminary observations indicate that its adoption remains limited in classrooms. This community service program aims to enhance students' digital visualization capabilities while equipping them with essential technological skills required in 21st-century education. The intervention was delivered through module-based hands-on training, paired with interactive video tutorials to facilitate self-paced learning. The curriculum covered the fundamental ChemDraw interface, organic compound drawing techniques, and reaction mechanism simulations. Post-activity evaluations revealed highly positive outcomes, with 96% of students finding the material accessible and 98% reporting a substantial increase in conceptual knowledge. Ultimately, this training effectively boosted student motivation and fostered a stronger mastery of digital competencies within chemistry education.